DISTRIBUTED CONGESTION-A WARE TRAFFIC LOAD BALANCING SCHEMES FOR ROUTING IN WIRELESS SENSOR NETWORKS - CHUGHTAI, HAFIZ MUHAMMAD OMER (2016)
Efficient routing m Wireless Sensor Network (WSN) plays an important role in enhancing the performance of the network. The data traffic generated by the sensing nodes in WSN usually follows the shortest discovered route between the source and the sink.